2005
DOI: 10.1177/00343552050480030101
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Disability Type and Career Thoughts to Vocational Identity

Abstract: This study compared dysfunctional career thoughts and perceptions of vocational identity for individuals with different types of disabilities and examined whether the relation of career thoughts to vocational identity was moderated by type of disability. Ninety adults with cognitive and physical impairments were administered the Career Thoughts Inventory and the My Vocational Situation. Results indicate that individuals with cognitive impairments had more decision-making confusion and external conflict than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
2
26
0
1
Order By: Relevance
“…This finding is not surprising and is consistent with a previous study that has indicated that both VI and PA are important constructs that contribute toward career thoughts (Yanchak et al, 2005). However, our study was the first attempted to explore this construct with young adult CNS cancer survivors and provides support for the need to address both of these constructs as it relates to career development.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is not surprising and is consistent with a previous study that has indicated that both VI and PA are important constructs that contribute toward career thoughts (Yanchak et al, 2005). However, our study was the first attempted to explore this construct with young adult CNS cancer survivors and provides support for the need to address both of these constructs as it relates to career development.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has identified that career thoughts are one of the key factors that impacts the career development process and that VI and PA contribute toward increased levels of productive career thoughts (Yanchak et al, 2005;Strauser et al, 2008). Therefore, we have hypothesized that young adult CNS cancer survivors differ in their level of career thoughts when compared with the noncancer young adult peers.…”
Section: Introductionmentioning
confidence: 98%
“…al, 1996). Validity for using the CTI with diverse groups of people has been further supported by studies of the instrument with college students of color and people with disabilities (Dipeolu, Reardon, Sampson, & Burkhead, 2002;Kleiman, et al, 2004;Osborn, Howard, & Leierer, 2007;Yanchak, Lease, & Strauser, 2005).…”
Section: Instrumentsmentioning
confidence: 98%
“…Definisan profesionalni identitet olakšava adolescentima uključivanje u proces profesionalnog istraživanja i predstavlja osnov njihove profesionalne buduć-nosti (Holland, Gottfredson & Power, 1980). Rezultati brojnih studija ukazuju da se adolescenti i odrasli sa stabilnim profesionalnim identitetom značajno bolje snalaze tokom tranzicija u profesionalnoj sferi, kao i da su efikasniji, produktivniji, zadovoljniji sopstvenim radom i posvećeniji radnim zadacima (Diemer & Blustein, 2007 Jančak smatra da osobe sa ometenošću često imaju poteš-koća u formiranju profesionalnog identiteta više zbog problema sa identitetom uopšte nego zbog neodlučnosti u donošenju profesionalnih odluka (Yanchak, 2005). Stresovi povezani sa poslovnom sferom funkcionisanja, kao što su male mogućnosti za zaposlenje, ometenost i značajni problemi finansijske prirode negativno utiču na razvoj profesionalnog identiteta (Goede et al, 1999).…”
Section: Uvodunclassified